(untitled) (ELang | An English Language Education Journal, 2024)
The research paper is entitled “The Use of Canva Application to Teach WritingProcedure Text in The First Grade of Junior High School”. Therefore, this paper was written to know wether or not canva application is significantly better than the conventional methode and to know the students’ responses to the use canva application in teaching writing procedure text. This research was conducted in the first semester of first grade of SMP SAIS 1 Kab. Bandung in the academic year of 2024/2025. This used quasi experimental design and the total sample in this research was 48 students that were taken from two classes. in collecting the data, the researcher used instruments pre-test, post-test, and questionnaire. After giving the post-test, the researcher analyzed the data by using the formula of t-test for independent groups. With the df = N1 + N2 – 2 = 48 – 2 = 46, at P = 0.05 of two tailed significance, the critical value of t is 2.009. As the value of t/tohigher than that of the t critical (5.384> 2.009), therefore H0 is rejected and Ha is accepted. This research also analyzed the data using dependent test. With the df = N(N – 1) =24(24 – 1) = 23, at P = 0.05 of two tailed significance, the critical value of t (9.778 > 2.064). Therefore, Null Hypotheses (H0) is rejected and Alternative Hypotheses(Ha) is Accepted. This means that the using of canva application in teaching writing procedure text is effective. Additionally, the students’ responses to the use of canva application in teaching writing procedure text are good and positive.